Pengaruh Penerapan Sistem Agribisnis Terhadap Pendapatan Usahantani Mentimun (Cucumis sativus L.) Di Kecamatan Rantau Kabupaten Aceh Tamiang - Supristiwendi; Monika Azizah (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2019)
Horticultural commodities consisting of fruit, vegetables, ornamental plants and medicinal plants are very prospective commodities to be developed through agribusiness, given the potential uptake of domestic and international markets continues to increase. Vegetables are one component of a healthy diet, so it's not surprising that the needs of vegetables today are increasing in line with people's awareness about health. Among the various types of vegetables that can be cultivated, cucumber plants are one of the fruit vegetable commodities that have commercial value and high prospects. Agribusiness is a commercially oriented farming or agricultural business venture with a profit orientation. One effort that can be taken in order to increase farm income is by applying the concept of integrated agribusiness system development, ie if the agribusiness system consisting of production facilities subsystems, cultivation subsystems, processing and marketing subsystems is developed in an integrated and harmonious manner. Agribusiness application needs to be done to advance farming in order to get maximum results in every agricultural production.